PENGARUH KOMPENSASI, MOTIVASI KERJA DAN GAYA KEPEMIMPINAN TERHADAP KINERJA APARATUR SIPIL NEGARA DI KPP PRATAMA LAMONGAN - Novena Margaretta; Woro Utari; Subijanto (Journal of Applied Management and Accounting Science, 2022)
This study aims to determine the effect of compensation, work motivation and leadership style on the performance of the State Civil Apparatus at KPP Pratama Lamongan and the most dominant factors in influencing employee performance are Leadership Style and compensation. In this study, the research population refers to all employees of KPP Pratama Lamongan and samples taken are 64 respondents from a total of 76 respondents due to damage or defects in sampling. This study uses multiple linear regression analysis techniques. Based on the results of the study, the following regression equation was obtained:Y = α + β1 X1 + β2 X2 + β3 X3 + e. Based on statistical analysis, the indicators in this study are valid and reliable. In the classical assumption test, the regression model is normally distributed. In this study, the variable that has the greatest influence is compensation with a regression coefficient of 0.529; work motivation variable with a regression coefficient of -0.096; and leadership style with a regression coefficient of 0.436.